Effect of year period, air temperature and relative humidity on the growing-finishing boars performance - Pacheco, Carlos Roberto V.M.; Freitas, Alfredo Ribeiro de; Fialho, Elias Tadeu (Pesquisa Agropecuaria Brasileira, 2014)
The effect of year period, air temperature and relative humidity on the growing-finishing boars performance was analysed. The animals were tested from 25 to 100 kg of live weight. The swine tested in the warm period showed better daily-weight gain and food conversion (864 g and 2,64) than those tested in the cold period (831 g and 2,74). In the range of temperature from 16 to 26°C with relative humidity lower than or equal to 80%, the results showed that the daily weight gain was better in the lowest (16 to 18°C) and in the highest (24 to 26°C) temperatures, but the differences were not significant. The relative humidity greater than 80% with temperature interval from 16 to 22°C decreased the daily weight gain and the efficiency of food conversion.